Unicidade de hipersuperfícies imersas em espaços riemannianos e lorentzianos: resultados, exemplos e contra-exemplos - Lima Júnior, Eraldo Almeida (2015)
In this work we present uniqueness results for constant mean curvature hypersurfaces in Riemannian and Lorentzian products. We dealt with product whose fiber has sectional curvature bounded from below. We considered a certain control in the norm of the gradient of the height function by the norm of the second fundamental form in order to obtain that such a surface is slice. We also obtained uniqueness through integrability conditions in the gradient of the height function. We also presented an extension of a lemma due to Nishikawa which was used to prove the results for the case of maximal surfaces, that is, with zero mean curvature. We have utilized as an essential tool, in the prove of the results, the generalized Omori-Yau maximum principle in one of the latest versions. In the end, we present examples showing and justifying the necessity of required hypothesis in the results.